Supercritical fluid dyeing of synthetic and natural textiles - a review - Banchero, Mauro (Coloration technology, 2013)
Supercritical fluid dyeing is an interesting alternative to the conventional aqueous process because of its environmental benefits. The aim of the paper is to provide the reader with an up‐to‐date overview of this subject, covering various aspects, such as the solubility and equilibrium partitioning of the dyes, mass transfer phenomena and solvent–polymer interactions occurring during coloration, up to the most recent reports on the technology of the dyeing process. Even though the best results have been obtained in the coloration of synthetic textiles, particular attention is given to the dyeing of natural textiles, which is, at the moment, the limiting step of this technology.